Ocular-cerebral immune dialogue: a new perspective and therapeutic potential of regional lymphatic systems - Wang, Yiran; Guo, Pei; Li, Weihong; Li, Tong (Frontiers in Immunology, 2025)
The Central Nervous System (CNS), due to its unique structure and function, possesses immune privilege, which is primarily maintained through mechanisms such as the blood-brain barrier, immune cell exclusion, and neuroglial cell regulation, effectively protecting the CNS from external insults. In recent years, research has discovered the presence of functional lymphatic systems in the meninges and the posterior segment of the eye, capable of draining cerebrospinal fluid and ocular antigens to the deep cervical lymph nodes, directly connecting with the systemic immune system. This finding has revised the traditional view that the CNS lacks lymphatic circulation and has provided a new perspective for understanding CNS immune privilege. Particularly, the posterior segment of the eye shares lymphatic drainage pathways with the brain, further revealing the complex immunological connections between the two. The ocular-cerebral connected regional lymphatic system plays a key role in ocular immune surveillance and pathological links within the CNS, with its dysfunction potentially exacerbating inflammatory responses and disease progression. Moreover, this system offers new avenues for early diagnosis, immune modulation, and drug delivery in CNS diseases, demonstrating significant clinical application potential and providing a scientific basis for the diagnosis and treatment of neurodegenerative and ophthalmic diseases.